2010
DOI: 10.14310/horm.2002.1285
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous recovery from isolated post-traumatic central hypogonadism in a woman

Abstract: OBJECTIVE. Hypopituitarism is a recognized complication of Traumatic Brain Injury (TBI). resolution of established anterior

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…It is apparent that TBI‐induced HH, even when limited to the anterior hypothalamus, 13,80 is a system problem commonly involving both the HPG axis and the HPA axis 81 . From our study, it is not possible to determine whether the CCI injury had an impact beyond that of craniectomy on promoting hypogonadism or hypoadrenalism, as has been reported for human TBI 6–8,10,14,76–78,82–96 . These results demonstrate that future studies need to take into account the effects of isoflurane alone in any model of TBI‐induced hypogonadism.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…It is apparent that TBI‐induced HH, even when limited to the anterior hypothalamus, 13,80 is a system problem commonly involving both the HPG axis and the HPA axis 81 . From our study, it is not possible to determine whether the CCI injury had an impact beyond that of craniectomy on promoting hypogonadism or hypoadrenalism, as has been reported for human TBI 6–8,10,14,76–78,82–96 . These results demonstrate that future studies need to take into account the effects of isoflurane alone in any model of TBI‐induced hypogonadism.…”
Section: Discussionmentioning
confidence: 66%
“…81 From our study, it is not possible to determine whether the CCI injury had an impact beyond that of craniectomy on promoting hypogonadism or hypoadrenalism, as has been reported for human TBI. [6][7][8]10,14,[76][77][78][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96] These results demonstrate that future studies need to take into account the effects of isoflurane alone in any model of TBI-induced hypogonadism.…”
Section: Ta B L E 1 the Relationship Between The Concentrations Of Plasma Steroids In Ratsmentioning
confidence: 99%
“…Pituitary recovery 12 years after TBI was also reported (Ruggeri et al, 2010), possibly due to pituitary revascularization and cellular pituicyte repopulation (Benvega et al, 2000). …”
Section: When Should Patients Be Screened After Tbi?mentioning
confidence: 87%
“…9 Post-traumatic central diabetes insipidus is frequently transient, 6,10 although spontaneous recovery from anterior pituitary hormone deficiency is rare. 10 In one series, only 3 of 19 children (aged 4 months-15 years) with acute central diabetes insipidus secondary to severe brain injury survived the acute attack of central diabetes insipidus. 8 Therefore, the occurrence of acute onset central diabetes insipidus may be a poor prognostic factor for survival in patients with TBI.…”
Section: Discussionmentioning
confidence: 99%
“…reported that 26% of patients with TBI developed central diabetes insipidus in the acute phase (the duration of in‐hospital stay)8 and that central diabetes insipidus occurred in 6.9% of long‐term survivors following TBI 9. Post‐traumatic central diabetes insipidus is frequently transient,6, 10 although spontaneous recovery from anterior pituitary hormone deficiency is rare 10. In one series, only 3 of 19 children (aged 4 months–15 years) with acute central diabetes insipidus secondary to severe brain injury survived the acute attack of central diabetes insipidus 8.…”
Section: Discussionmentioning
confidence: 99%